An Investigation on Possible Links between Risk Management, Performance Measurement and Reward Schemes - Selena Aureli; Federica Salvatori (Journal of Accounting and Management Information Systems (JAMIS), 2012)
The ongoing global financial crisis underlined the urgent need of changing traditional executives compensation schemes. Governments and authorities reacted through regulation and standards, while professionals and academics have suggested several new pay mechanisms (e.g. deferred bonus). Given some limitations of the above-mentioned solutions, the paper aims at understanding whether they can be improved by introducing incentives strictly tied to companies' risk metrics for executive members of the Boards and top managers with strategic responsibilities. The link between monetary incentives and the achievement of desired risk-adjusted performance is thus proposed and explored. Following a qualitative methodology, four case studies were carried out using semi-structured interviews with Italian risk managers and human resources managers. Results show that a reward system based on risk measures is welcome and feasible, if not already adopted. It needs to be carefully tailored to each company. Lastly, its adoption and implementation rely on various contextual conditions and can be hindered by some difficulties in risk measurement. The paper contributes to the reward and risk management literature by investigating new tools to satisfy the need of sounder compensation practices.
Keywords: M12; M41; M52; 650; Risk; executive compensation; reward; performance indicators